Colonial Systems of Control Criminal Justice in Nigeria - Saleh-Hanna, Viviane (Alternative Perspectives in Criminology, 2008)
A pioneering book on prisons in West Africa, Colonial Systems of Control: Criminal Justice in Nigeria is the first comprehensive presentation of life inside a West African prison. Chapters by prisoners inside Kirikiri maximum security prison in Lagos, Nigeria are published alongside chapters by scholars and activists. While prisoners document the daily realities and struggles of life inside a Nigerian prison, scholar and human rights activist Viviane Saleh-Hanna provides historical, political, and academic contexts and analyses of the penal system in Nigeria. The European penal models and institutions imported to Nigeria during colonialism are exposed as intrinsically incoherent with the community-based conflict-resolution principles of most African social structures and justice models. This book presents the realities of imprisonment in Nigeria while contextualizing the colonial legacies that have resulted in the inhumane brutalities that are endured on a daily basis.